An Industrial Assessment of Software Framework Design: A case study of a rule-based framework - hussein, mustafa; Lundén, Anton (My University, 2017)
Software frameworks provide reusable functionality and play an important role in increasing the productivity and maintainability of large software systems. Commonly the functionality and services encapsulated by the framework is accessed through an API, obscuring the inner workings of the framework. Many companies have rules that their products and software systems are required to follow, these rules can have a wide range of technical depth and are often classified as business rules, guidelines, regulations and policies, some frameworks are driven by these rules. These frameworks are used in a system to implement a set of rules,in addition to providing the usual functionalities of a framework. We call such frameworks rule-based.These frameworks can be used by companies to enforce rules in a production environment, one of such companies is Ericsson. Ericsson develops applications that must adhere to company-specific design rules, the use of a rule-based framework eases the common implementation of these rules. e.g. by reducing boilerplate code created by several applications implementing the same design rules.Using Ericssons framework as a basis for the case study the purpose of the study was to identify and demonstrate what values rule-based frameworks can provide for different stakeholders. In addition to this the study provided insight into what factors should drive the design, development and usage of rule-based frameworks. Data was collected throughout the case study through archival data, interviews and to a lesser extent, surveys. The data was collected from a variety of stakeholders to capture the difference perspectives and experiences. The data was analyzed and modeled using iStar Goal Modeling and e-3 Value Modeling to aid in understanding the ecosystem and values of the framework.
Keywords: Data- och informationsvetenskap; Computer and Information Science